DESIGN CENTRIFUGAL PUMP ASSISTED BY CF TURBO 10.2 SOFTWARE - Siprianus Ndaha Ate (University of Merdeka Malang, 2019)
In the industrial world the use of centrifugal pumps is often used to distribute water that is to support the smooth running of industrial processes or to cool a machine. Centrifugal pumps have a very broad scope of use with the head and the resulting capacity is very large and varied. In this final project, a centrifugal pump with a capacity of 30 m3 / hour, a pump head of 10 meters, a shaft rotation of 1500 rpm and a pressure difference of 10 bar in and out is planned. In the planning of centrifugal pumps, CF Turbo 10.2 software is used. Fluid is water (